Anticancer and anti-inflammatory activities of girinimbine isolated from Murraya koenigii - Iman V; Mohan S; Abdelwahab SI; Karimian H; Nordin N; Fadaeinasab M; Noordin MI; Noor SM (Dove Medical Press, 2016)
Venoos Iman,1 Syam Mohan,2 Siddig Ibrahim Abdelwahab,2 Hamed Karimian,1 Noraziah Nordin,1 Mehran Fadaeinasab,3 Mohamad Ibrahim Noordin,1 Suzita Mohd Noor4 1Department of Pharmacy, Faculty of Medicine, University of Malaya, Kuala Lumpur, Malaysia; 2Medical Research Center, Jazan University, Jazan, Saudi Arabia; 3Department of Chemistry, 4Department of Biomedical Science, Faculty of Medicine, University of Malaya, Kuala Lumpur, Malaysia Abstract: Therapy that directly targets apoptosis and/or inflammation could be highly effective for the treatment of cancer. Murraya koenigii is an edible herb that has been traditionally used for cancer treatment as well as inflammation. Here, we describe that girinimbine, a carbazole alkaloid isolated from M. koenigii, induced apoptosis and inhibited inflammation in vitro as well as in vivo. Induction of apoptosis in human colon cancer cells (HT-29) by girinimbine revealed decreased cell viability in HT-29, whereas there was no cytotoxic effect on normal colon cells. Changes in mitochondrial membrane potential, nuclear condensation, cell permeability, and cytochrome c translocation in girinimbine-treated HT-29 cells demonstrated involvement of mitochondria in apoptosis. Early-phase apoptosis was shown in both acridine orange/propidium iodide and annexin V results. Girinimbine treatment also resulted in an induction of G0/G1 phase arrest which was further corroborated with the upregulation of two cyclin-dependent kinase proteins, p21 and p27. Girinimbine treatment activated apoptosis through the intrinsic pathway by activation of caspases 3 and 9 as well as cleaved caspases 3 and 9 which ended by triggering the execution pathway. Moreover, apoptosis was confirmed by downregulation of Bcl-2 and upregulation of Bax in girinimbine-treated cells. In addition, the key tumor suppressor protein, p53, was seen to be considerably upregulated upon girinimbine treatment. Induction of apoptosis by girinimbine was also evidenced in vivo in zebrafish embryos, with results demonstrating significant distribution of apoptotic cells in embryos after a 24-hour treatment period. Meanwhile, anti-inflammatory action was evidenced by the significant dose-dependent girinimbine inhibition of nitric oxide production in lipopolysaccharide/interferon-gamma-induced cells along with significant inhibition of nuclear factor-kappa B translocation from the cytoplasm to nucleus in stimulated RAW 264.7 cells. Girinimbine was also shown to have considerable antioxidant activity whereby 20 µg/mL of girinimbine was equivalent to 82.17±1.88 µM of Trolox. In mice with carrageenan-induced peritonitis, oral pretreatment with girinimbine helped limit total leukocyte migration (mainly of neutrophils), and reduced pro-inflammatory cytokine levels (interleukin-1beta and tumor necrosis factor-alpha) in the peritoneal fluid. These findings strongly suggest that girinimbine could act as a chemopreventive and/or chemotherapeutic agent by inducing apoptosis while suppressing inflammation. There is a potential for girinimbine to be further investigated for its applicability in treating early stages of cancer. Keywords: carbazole alkaloid, apoptosis, inflammation, chemopreventive, chemotherapeutic